NILAI-NILAI PENDIDIKAN AKIDAH DALAM QS. ASY-SYU’ARA - Anshory, Muhammad Isa; Hafid, Muhammad Syarifudin (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2022)
This study intends to identify and analyze the signs in the verse contained in the letter as-Syua'ara that have relevance to the values of aqidah education. In particular, this study describes a) describing the values of creed education b) describing the values of creed education that can be understood in the letter as-Syu'ara. This study uses a qualitative approach with technical literature (Library research). The method used is content analysis technique. The results of this study indicate that the educational values of faith in this letter as-Syua'ara reinforce the purity of aqidah and glorify God and are oriented to the afterlife